Strategi Peningkatan Konsumsi Ikan Sebagai Upaya Penanggulangan Stunting Di Desa Baruh, Kecamatan Sampang, Kabupaten Sampang - Ifa Nur Rosidah; Apri Arisandi; Akhmad Farid (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2022)
Fish consumption is considered as one of the solutions in overcoming nutritional problems in toddlers because fish is one of the sources of animal protein obtained from natural resources in Indonesia. Stunting incident in East Java (Jatim) is relatively high, the Head of Jatim Health Office, said there are 12 districts in Jatim have high stunting rates, namely, Sampang, Pamekasan, Bangkalan, Sumenep, Jember, Bondowoso, Probolinggo, Nganjuk, Lamongan, Malang Regency, Trenggalek, to Kediri. Sampang is one of the 12 locus stunting districts of east Java. In Sampang Regency there is a village that will become a stunting research area, namely Baruh Village, Sampang District of Sampang Regency. The purpose of this study was to (1)Analyze the effect of fish consumption levels on the number of stunting sufferers in toddlers, (2) Determine strategies to increase fish consumption as an effort to combat stunting in toddlers. The data analysis method in this study uses regression analysis and SWOT analysis method. The results of this study showed that there is a relationship between fish consumption and stunting incidence in toddlers aged 2-5 years because of multiple R values of 0.16, this shows that high fish consumption will reduce the number of stunting sufferers.